Ảnh hưởng của mức độ phức tạp nhiệm vụ lên hành vi nghỉ việc thầm lặng: Vai trò điều tiết của nhúng sâu vào công việc và trao quyền tâm lý - Lại Phương , Thảo; Nguyễn Hồng , Quân; Lê Việt, Hà; Đặng Hồ Hải , Long; Nguyễn Tài , Uyên; Dương Thu , Trang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
Based on the Transactional Theory of Stress and Coping and the Conservation of Resources Theory, this study aims to examine the impact of task complexity on quiet quitting through the mediating role of job burnout. Furthermore, it examines the moderating roles of psychological empowerment and job embeddedness across different psycho-behavioral stages. Using CB-SEM modeling, data were collected from 375 full-time employees at startups between September and December 2025 in Hanoi, Da Nang, and Ho Chi Minh City. The results indicate that task complexity has a positive influence on quiet quitting via job burnout; however, these effects are attenuated by psychological empowerment and job embeddedness. Additionally, multi-group analysis reveals that the relationships within the model vary across groups with different levels of tenure. Practical recommendations are provided, focusing on effective job design, burnout reduction, fostering psychological empowerment, and enhancing job embeddedness within the Vietnamese work environment